Use of solar Parabolic Trough Collectors for hot water production in Cyprus. A feasibility study. - Lloyd, Stephen J.; Kalogirou, Soteris A. (My University, 1992)
This paper deals with a feasibility study for the use of solar Parabolic Trough Collectors for hot water production in Cyprus. An analysis is carried out for two types of applications, domestic and hotel. The systems are optimised using the F-chart program and compared to similar systems using Flat Plate Collectors. It is shown that for large scale water production the Parabolic Trough Collectors are more efficient than the Flat Plate ones. The life cycle savings from their use as applied to a real life situation is almost 5,350 Cyprus Pounds with 60% of the available solar energy being utilised.
Keywords: Solar parabolic; Hot water production